Characterization and mapping of an informational suppressor in Aspergillus nidulans - MELISSA GRACITE DE MELO FRANZONI; MARIALBA AVEZUM ALVES DE CASTRO-PRADO (Biological Research, 2000)
The present work was undertaken to characterize a suppressor gene present in a mutant strain of A. nidulans obtained with NTG (N-Methyl-N'-Nitro-N-Nitrosoguanidine). Analyses of this mutant have shown that this suppressor, designated suO1, induces phenotypic co-reversion of several auxotrophic mutations and makes the strain sensitive to aminoglycoside antibiotics and lower temperatures. suO1 has shown to be on linkage group VIII. The vegetative growth of the mutant strain is very unstable because the suppressor gene induces the production of prototrophic mitotic sectors. The strains bearing the suO1 gene produce cleistothecia containing a reduced number of viable ascospores during the sexual cycle. The segregation of the genetic markers has also been observed in the mutant strain self crossed. From the above results it may be concluded that suO1 is an informational suppressor